A CROSSECTIONAL STUDY ON THE MIDWIVES’ PRACTICES OF UMBILICAL CORD CLAMPING IN THE GREATER KABALE DISTRICT IN UGANDA. - ATUHEIRE , CONFIDENCE; DR. MANUEL, AMININIYE MACREGOR; EUNICE UDO-PERETOMODE (Student’s Journal of Health Research Africa, 2023)
Introduction: Timely and appropriate umbilical cord clamping was found to be key in reducing neonatal death. Despite current guidelines recommending when to clamp the umbilical cord, some midwives in the Greater Kabale District continued to practice immediate cord clamping. Aim: The study assessed the practices of umbilical cord clamping among midwives in Greater Kabale District in Uganda. Methods: The study employed a cross-sectional study design with a sample size of 174 midwives practicing at 17 public health facilities in the study area. A self-structured questionnaire with a reliability of coefficient 0.87 was used to gather quantitative data for the study. Data was analyzed with descriptive tools of percentage, frequency, mean, and standard deviation. Ethical approval was obtained from the appropriate research committees. Results: The study revealed only 35% of the respondents practiced umbilical cord clamping according to the World Health Organization’s (WHO) recommended guidelines. The results further revealed that age, job title, facility type, and years in service were statically significant with p-values of less than 0.05. Conclusion: Although the WHO recommended delayed umbilical cord clamping, the practice of this procedure is still very low among midwives in the Greater Kabale District. Therefore, there is an urgent need to educate and sensitize the midwives on the health benefits of delayed clamping practice to. Recommendations: Regular Continuing Medical Education for the midwives is necessary to equip them with updated information and getting informed which can have a great impact on their practice of umbilical cord clamping according to recommended guidelines. Mentorship and support supervision for the health facilities offering maternal health services should be done and emphasize the benefits of DCC to the newborn.